1997
DOI: 10.1002/(sici)1097-0282(19970415)41:5<569::aid-bip8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison between retro-inverso and parent peptides: Molecular basis for the biological activity of a retro-inverso analogue of the immunodominant fragment of VP1 coat protein from foot-and-mouth disease virus

Abstract: Antibodies induced against intact foot‐and‐mouth disease Virus (FMDV) particles bind to the retro‐inverso analogue of fragment 141–159 of the viral coat protein VP1 of FMDV, variant A, equally well as to the parent peptide. A conformational investigation of this retro‐inverso peptide was carried out by nmr spectroscopy and restrained molecular modeling in order to identify the structural basis for the antigenic mimicry between these retro‐inverso and parent peptides. In 100% trifluoroethanol a well‐defined lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…However, in the case of the retro-inverso peptide, the intensity of the Cotton effect at 222 nm was stronger ([⌰] ϭ ϩ6.20 ϫ 10 3 versus Ϫ4.49 ϫ 10 3 calculated for the L-peptide). This result is in good agreement with previous NMR investigations performed in TFE-d 2 on a related antigenic peptide (variant SL), which revealed that the helical region present in the C-terminal half (with respect to the parent sequence) of both peptides is more defined in the retro-inverso isomer (10,21). To further characterize the structural behavior of the retro-inverso isomer in solution, an H 2 O/TFE solvent titration was performed at room temperature.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, in the case of the retro-inverso peptide, the intensity of the Cotton effect at 222 nm was stronger ([⌰] ϭ ϩ6.20 ϫ 10 3 versus Ϫ4.49 ϫ 10 3 calculated for the L-peptide). This result is in good agreement with previous NMR investigations performed in TFE-d 2 on a related antigenic peptide (variant SL), which revealed that the helical region present in the C-terminal half (with respect to the parent sequence) of both peptides is more defined in the retro-inverso isomer (10,21). To further characterize the structural behavior of the retro-inverso isomer in solution, an H 2 O/TFE solvent titration was performed at room temperature.…”
Section: Resultssupporting
confidence: 93%
“…To better understand the structural basis for antigenic mimicry between the L-peptide and its retro-inverso analogue, Carver et al (10) recently analyzed the L-and retro-inverso peptides 141-159 of the SL variant (with Ser and Leu residues at positions 148 and 153) by NMR spectroscopy and restrained molecular modelling. The NMR structures of the peptides were determined in trifluoroethanol-d 2 (TFE-d 2 ) at different temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 -32 inherently chiral structural elements, are roughly mirror images. 35 Both contain N-and C-terminal helical domains, right-handed in the RI and left-handed in the native sequence, and a ␥-turn around Gly 149 . In spite of the fact that the R 145 GD, which is involved in antibody recognition, has a different backbone conformation from that of the retro-inversed triad, they both adopt quasi-planar structures displaying very similar topologies.…”
Section: Ri Peptides As Immunogens Immunomodulators and Diagnostic mentioning
confidence: 99%
“…Both the inherent flexibility around R 145 and the almost planarity of the recognition sequence explain the similarity in antigenic activity of the native peptide and its RI isomer. 35 In another study Guichard and coworkers reported the preparation of a series of PMRI analogs of the influenza matrix peptide 58 -66 [M(58 -66)] known to be a human leukocyte antigen (HLA)-A2-restricted epitope that binds preferentially nonapeptides with Leu, Met, or Ile in position P2 and Val, Leu, or Ile in position P9. 36 PMRI pseudopeptide [Gly 58 ⌿ (NH-CO)Leu 59 ]M(58 -66) was able to stabilize HLA-A2 at a concentration of 10 nM and was found to be more effective than the wild-type sequence in stimulating CD8 ϩ CTL to secrete interferon-␥ (INF-␥) and synthesize tumor necrosis factor (TNF)-␣ mRNA, cytokines involved in antiviral and antitumor responses.…”
Section: Ri Peptides As Immunogens Immunomodulators and Diagnostic mentioning
confidence: 99%